Numerical Analysis of an Optimal Control Problem Governed by the Stationary Navier-Stokes Equations with Global Velocity-Constrained (Communications in Computational Physics, 2018)
A state-constrained optimal control problem governed by the stationaryNavier-Stokes equations is studied. Finite element approximation is constructed, theoptimal-order a priori H1-norm and L2-norm error estimates are given, for which theoptimal state is a nonsingular solution of the Navier-Stokes equations to the optimalcontrol.